2009
DOI: 10.1002/app.29658
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosive properties of epoxy resin coatings cured by aniline/p‐phenylenediamine copolymer

Abstract: Aniline/p-phenylenediamine copolymer [poly(ANI-co-p-PDA)] was prepared by chemical oxidative polymerization. FTIR and 1 H-NMR analysis indicate that the poly(ANI-co-p-PDA) is oligomer with end-capped amino groups, which can cure epoxy resin. The anticorrosion performance of carbon steel (CS) samples coated by epoxy resin coating cured with poly(ANI-co-p-PDA) and epoxy resin coating cured with triethylenetetramine exposed to 5 wt % NaCl and 0.1 mol/L HCl aqueous solution is studied by the potentiodynamic polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This concept is supported by two observations: (1) Only small amounts of PDA are needed for the initiation of aniline polymerization. If PDA participated only as a comonomer in the propagation step (and PDA indeed copolymerizes with aniline ), much larger quantities would be needed to produce a marked effect. (2) The phenazine nucleates are able to self-assemble and to guide the subsequent growth of nanogranules, nanofibers, or nanotubes .…”
Section: Resultsmentioning
confidence: 99%
“…This concept is supported by two observations: (1) Only small amounts of PDA are needed for the initiation of aniline polymerization. If PDA participated only as a comonomer in the propagation step (and PDA indeed copolymerizes with aniline ), much larger quantities would be needed to produce a marked effect. (2) The phenazine nucleates are able to self-assemble and to guide the subsequent growth of nanogranules, nanofibers, or nanotubes .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the corrosion inhibition of AT may be ascribed to the presence of electron-rich N and aromatic rings. Nevertheless, the amino and imino groups of aniline tetramer can also crosslink and cure with the epoxy resin and produce the shielding effect [26]. Therefore, epoxy coating with or without AT was characterized by dynamic thermomechanical analysis.…”
Section: Mechanism Of Corrosion Inhibitionmentioning
confidence: 99%
“…The peak at d ¼ 3.4 ppm corresponds to the OCH 3 group and the two peaks at d ¼ 3.7 ppm are for -NH and -NH 2 . 12 The singlet signal at d ¼ 2.5 ppm was correlated to the solvent protons.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the copolymerization of o-phenyldiammine has remarkably improved some of the properties like stability, conductivity and solubility 7 . Yao et al have synthesized aniline-p-phenyldiammine copolymer and reported its corrosion protection performance using electrochemical measurements 12 , their Icorr values in 5 % NaCl medium was found to be 0.06µA/cm 2 . in 5% HCl 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation